Should Asymptomatic Bacteriuria Be Systematically Treated in Kidney Transplant Recipients? Results From a Randomized Controlled Trial. Issue 10 (23rd May 2016) - Origüen, J.; López‐Medrano, F.; Fernández‐Ruiz, M.; Polanco, N.; Gutiérrez, E.; González, E.; Mérida, E.; Ruiz‐Merlo, T.; Morales‐Cartagena, A.; Pérez‐Jacoiste Asín, M. A.; García‐Reyne, A.; San Juan, R.; et al.
Abstract : The indication for antimicrobial treatment of asymptomatic bacteriuria (AB) after kidney transplantation (KT) remains controversial. Between January 2011 and December 2013, 112 KT recipients that developed one episode or more of AB beyond the second month after transplantation were included in this open‐label trial. Participants were randomized (1:1 ratio) to the treatment group (systematic antimicrobial therapy for all episodes of AB occurring ≤24 mo after transplantation [53 patients]) or control group (no antimicrobial therapy [59 patients]). Systematic screening for AB was performed similarly in both groups. The primary outcome was the occurrence of acute pyelonephritis at 24‐mo follow‐up. Secondary outcomes included lower urinary tract infection, acute rejection, Clostridium difficile infection, colonization or infection by multidrug‐resistant bacteria, graft function and all‐cause mortality. There were no differences in the primary outcome in the intention‐to‐treat population (7.5% [4 of 53] in the treatment group vs. 8.4% [5 of 59] in the control group; odds ratio [OR] 0.88, 95% confidence interval [CI] 0.22–3.47) or the per‐protocol population (3.8% [1 of 26] in the treatment group vs. 8.0% [4 of 50] in the control group; OR 0.46, 95% CI 0.05–4.34). Moreover, we found no differences in any of the secondary outcomes. In conclusion, systematic screening and treatment of AB beyond the second month after transplantation provided no apparent benefit among KT recipients (NCT02373085). Abstract : This randomized controlled trial shows no difference in the incidence of acute pyelonephritis between kidney transplant recipients who had all their episodes of asymptomatic bacteriuria treated and those who did not receive antimicrobial treatment for asymptomatic bacteriuria beyond the second month after transplantation. See the editorial from Blumberg onpage 2779 .